Efeito do resíduo industrial de alumínio nas propriedades de compósitos poliméricos - OLIVEIRA, Gabriel da Cruz (2021)
Composites encompass a class of materials with important properties for various application sectors, but what draws attention to the composite is its potential to combine different types of materials, and this factor gains greater value when directed towards the reuse of materials that are discarded industries and that directly interfere in sustainable development. This work consists of the production of composite materials from the incorporation of industrial aluminum waste in a polymeric matrix, which were tested according to their physical, mechanical and resistance to burning properties. Thus, tests of morphological, chemical and mineralogical characterization of the waste were carried out. The matrix used was the unsaturated isophthalic polyester resin with the addition of the cobalt accelerator (1.5 % v / v) and butanox M-50 catalyst (1 % v / v). The aluminum residue was obtained from the company Colorjato in the state of São Paulo and, for the methodology of this work, it was classified in a 100 mesh sieve of the Tyler series. The manual method Hand lay-up associated with compression was used for the manufacture of composites, with volumetric fractions of residue of 0 %, 10 %, 20 % and 30 %. The results showed that the aluminum particulate has different sizes according to the microstructural analysis of the particles, presenting certain impurities such as Silicon and Chromium in their grains. The physical properties showed that the insertion of waste led to a gradual increase in the apparent density, which had a direct influence on water absorption and apparent porosity. In the mechanical strength test of the composite, the 10 % compositions showed better mechanical performance of traction and flexion, with mechanical strength of up to 27.11 and 133.19 MPa, respectively. The analysis of the fractures of the composites showed that volumetric fractions less than 30 % present a better distribution of the particulate, with good homogenization and dispersion of the present phases. The horizontal flammability test allowed to evaluate that the flame resistance of the composite is proportional to the addition of residue within the matrix, which indicates that the aluminum residue in general presents resistance due to its structure and / or its constituents. The results expressed that the composition limit of 30 % showed a lower burning rate of 11.17 mm / min, with a reduction of up to 49.42 % compared to polyester. Thus, the study describes a potential in relation to the combination of the present phases for possible applications, although a more specific study is needed.